ACP private sector declaration on the operationalisation of the Cotonou Agreement (ACP Secretariat [Brussels]BE, 2002)
Deals with five issues viz. capacity-building; structuring of the ACP private sector; financial resources; cooperation between the ACP and EU private sectors; and, monitoring and evaluation.
Keywords: TRADE AGREEMENTS